Catechesis at a School or outside School? - Radosław Chałupniak (Nicolaus Copernicus University in Toruń, 2012)
In the contemporary religious education, a great amount of deliberations is devoted to the subject of religious education (by whom? to whom?), its contents (what?), aims (what for?), methods and means (how?), conditioning (where? when?), but only occasionally questions are raised about the need and justification for religious education. Meanwhile, the question of justification for religious education is gaining more and more importance in the situation of increasing secularization of social and personal life. It is important to go back and recall these arguments that justify religious education in various educational environments. The contemporary conditioning of catechesis is undergoing significant changes. The ignorance of this fact leads to a situation where religious education is treated marginally and its effectiveness becomes limited. The article presents main arguments in favour of the presence of religious education in state schools in Poland. Its justification can be carried out at various levels: philosophical and anthropological, social and political, cultural and historical, legal, pedagogical, and finally theological and pastoral.